Challenges in preserving Afro-Brazilian heritage at MAFRO / UFBA (Cadernos de Sociomuseologia, 2019)
The Afro-Brazilian heritage has been, over the centuries, neglected by academia and institutions, particularly as prejudices and structural racism in our society. This article will treat, in the context of Social Museology, actions for the conservation of Afro-Brazilian Heritage, held at the Afro-Brazilian Museum of the Federal University of Bahia (MAFRO / UFBA), from 2011 to 2016. MAFRO is a university museum that was born in 19740, with an incubation of preserving and disseminating memory, treating services related to African and Afro-Brazilian cultures and promoting contacts with the local community. As the preservation actions treated, carried out between 2011 and 2016, were developed in favor of research directed to the collection and as its problems, the conservation of movable goods and communication processes. These actions were marked by challenges and problems that were revealed at the interface between preservation and communication of heritage. Keywords: Heritage. Preservation. Museum. Communication.